KINETIC MODEL OF AL-SI ORDERING IN ALKALI FELDSPARS UNDER "DRY" CONDITIONS - Kamentsev I.E.; Sorokin N.D. (My University, 2004)
The following kinetic model was proposed for K-Na feldspar under dry conditions: Ci = C0exp[(K0RT 02)/(Qg)]exp[-Q/RT0] where C i is the aluminum content in the 2t1 position after completion of the ordering process, which can be determined from X-ray diffraction data; C0 is the aluminum content in the 2t1 position at the temperature of the beginning of ordering, T0; g is the cooling rate; Q is the activation energy of Al-Si ordering in alkali feldspars; K0 is the constant; and R is the universal gas constant. The analysis of published high-pressure experimental data allowed us to determine within this model the values of the activation energy of disordering, which is equal within errors to the activation energy of ordering. The relations obtained for natural alkali feldspar samples allowed us to determine T 0 for a known cooling rate (g), which can be estimated from the measurements of sizes of primary exsolution perthites in alkali feldspar and Ci. Cooling rate and temperature of the beginning of Al-Si ordering were estimated for the alkali feldspars of the Mama pegmatite on the basis of X-ray diffraction determinations of Al-Si ordering (Ci) and the sizes of primary exsolution perthites. The influence of pressure on the Al-Si order-disorder process in alkali feldspars is discussed.